Efektivitas Teknik Role playing Dalam Bimbingan Kelompok Terhadap Perilaku Bullying Siswa Kelas VIII SMP Negeri 5 Surabaya - Atikah, Jihan Fairuz; Wirastania, Aniek (Universitas Nusantara PGRI Kediri, 2022)
The Cases of bullying that occur in Indonesia have increased every year. Data from the KPAI (Indonesian Child Protection Commission) East Java is included in the list of provinces that increase bullying cases yearly. This research aims to test the effectiveness of role-playing techniques in group guidance on bullying behavior in class VIII students of SMP Negeri 5 Surabaya. Bullying is a problem that must be overcome immediately in order not to cause victims from various circles. Bullying has a significant impact on a person's psyche. This research method uses quantitative research methods with the type of pre-experimental research. This research method uses quantitative research methods. The research design in this study used a one-group pre-test and post-test design given to class VIII students with high bullying behavior scale scores. This study uses non-parametric data analysis techniques with the Wilcoxon test. The results of the comparison of the scores on the bullying behavior scale before being given treatment and after being given treatment showed a significant effect, and that result, there was an effect of role-playing techniques in group guidance services on the bullying behavior of class VIII students of SMP Negeri 5 Surabaya.